Enabling chiral separations in discovery chemistry with open‐access chiral supercritical fluid chromatography. Issue 8 (13th June 2019) - Michaels, Philip; Neef, James; Galyan, Keith; Ginsburg‐Moraff, Carol; Zhou, Xilin; Dunstan, David; Poirier, Jennifer; Reilly, John
Abstract: Work from this paper details a novel walk‐up open‐access (OA) approach to enable chiral analytical method development and preparative separation of enantiomers in early discovery chemistry using supercritical fluid chromatography (SFC). We have demonstrated the success of this OA approach using immobilized chiral stationary phases (CSPs). After screening a diverse set of racemic drug candidates, we have concluded that a simplified OA chiral SFC platform can successfully purify approximately 60% of the analysed racemates. This streamlined OA workflow enables medicinal chemists with limited expertise in chiral method development to successfully and rapidly purify enantiomers for their projects using Waters UPC 2 and Prep100‐SFC instrumentation. Abstract :